Biogeochemistry of thermokarst lakes of western Siberia - Pokrovsky, Oleg S.; Shirkova, L. S.; Kirpotin, S. N. (Biochemistry research trends series., 2014)
This book described the current status and possible future changes of the thermokarst (thaw) lakes of western Siberia as dominant forms of landscape and regulators of greenhouse gas exchange within the atmosphere. Thawing permafrost and resulting microbial decomposition of previously frozen organic carbon is one of the most significant terrestrial ecosystem positive feedbacks to a warming climate. Ongoing processes of the permafrost thawing in Western Siberia are likely to increase the surface of water bodies via forming so-called thermokarst lakes, mobilizing the organic carbon (OC) from the.